Depleted iron stores are associated with inspiratory muscle weakness independently of skeletal muscle mass in men with systolic chronic heart failure. Issue 3 (23rd March 2018) - Tkaczyszyn, Michał; Drozd, Marcin; Węgrzynowska‐Teodorczyk, Kinga; Flinta, Irena; Kobak, Kamil; Banasiak, Waldemar; Ponikowski, Piotr; Jankowska, Ewa A.
Abstract: Background: Skeletal and respiratory muscle dysfunction constitutes an important pathophysiological feature of heart failure (HF). We assessed the relationships between respiratory muscle function, skeletal muscle mass, and physical fitness in men with HF with reduced left ventricular ejection fraction (HFrEF), and investigated the hypothesis of whether iron deficiency (ID) contributes to respiratory muscle dysfunction in these patients. Methods: We examined 53 male outpatients with stable HFrEF without asthma or chronic obstructive pulmonary disease (age: 64 ± 10 years; New York Heart Association [NYHA] class I/II/III: 36/51/13%; ischaemic aetiology: 83%; all with left ventricular ejection fraction ≤40%) and 10 middle‐aged healthy men (control group). We analysed respiratory muscle function (maximal inspiratory and expiratory pressure at the mouth [MIP and MEP, respectively]), appendicular lean mass/body mass index (ALM/BMI; ALM was measured using dual‐energy X‐ray absorptiometry), physical fitness (components of Functional Fitness Test for Older Adults), and iron status. Results: MIP, MEP, and ALM/BMI (but not MIP adjusted for ALM/BMI) were lower in men with HFrEF vs. healthy men. MIP, MEP, and MIP adjusted for ALM/BMI (but not ALM/BMI) were lower in men with HFrEF with vs. without ID. In a multivariable linear regression model lower serum ferritin (but not transferrin saturation) was associated with lower MIP independently of ALM/BMI, left ventricular ejection fraction, N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), and haemoglobin concentration. In multivariable linear regression models, lower MIP was associated with worse results in Functional Fitness Test when adjusted for ALM/BMI or relevant clinical variables (NYHA class, estimated glomerular filtration rate, NT‐proBNP, and haemoglobin concentration). Conclusions: In men with HFrEF, low ferritin reflecting depleted iron stores is associated with inspiratory muscle weakness independently of skeletal muscle mass. Inspiratory muscle dysfunction correlates with worse physical fitness independently of either skeletal muscle mass or disease severity.